(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:21:04
(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2因式分解(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2因式分解(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^
(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2 因式分解
(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2 因式分解
(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2 因式分解
原式+abc^2-abc^2
=(a+b)c^3-(a+b)^2*c^2+ab(a+b)c^2
=(a+b)(ac+bc-a-b)c^2+ab(a+b)c^2
=(a+b)(ac+bc-a-b+ab)c^2
b/(a^2-ab)+c/(b^2-ab)+(a+b^2)/(a^2b-ab^2)
(a+b)c^3-(a^2+ab+b^2)c^2+a^2b^2 因式分解
若a^2+b^2=c^2,ab=3则(a+b+c)(a-b+c)(a+b-c)(-a+b-c)
2(a^2b-2ab^2+c)-(2c+3a^2b-ab^2)
2(a²b-2ab²+c)-(2c+3a²b-ab²)
(a+b+c)(a^2+b^2+c^2-ab-ac-bc)+3ab=
若a>b>c,a+2b+3c=0,ab>ac与ab
已知:A=-2ab,B=3ab(a+b),C=2a^2b*3ab^3,求3A*B-1/2A*C
若a-b=3,b-c=2,求a+b+c-ab-bc-ac
(a-b)^3+2ab(a-b)
24ab^2c^2(a+b-c)-32abc(a-c-b)^2+8abc^3(c-a-b)
初二数学竞赛计算题,在线等!1. 1/(a-b)+1/(a+b)-[(a-b)/(a^2-ab+b^2)]-[(a+b)/(a^2-ab+b^2) ]2. (b-c)/(a^2-ab-ac+bc)+(c-a)/(b^2-bc-ab+ac)+(a-b)/(c^2-ac-bc+ab)3. (a-b)/(a+b)+(b-c)/(b+c)+(c-a)/+(c+a)+[(a-b)(b-c)(c-a)/(a+b)(b+c)(c+a)]4. [-ac/(a-b)
因式分解abc+a^2b-ab^2-a+b-c
通分 b/3a²c²,c/2ab,a/5b³c
a^3+b^3+c^3-3ab=(a+b+c)(a^2+b^2+c^2-ab-ac-bc)=1/2(a+b+c)[(a-b)^2+(a-c)^2+(b-c)^2]的证明过程
-a(a-b)^2-a^2(-a-b)^2-a^3(b-a)^3的公因式是a.ab.a(a-b)c.a(a+b)d.a(a-b)(a+b)
(a-b+c/a+b-c)-(a-2b+3c/b-c+a)+(b-2c/c-a-b)
计算ab-(2ab-3a²b)的结果是()A.3a²b+3ab B.-3a²b-ab C.3a²b-ab D.-3a²+3ab